Гребенчатый фильтр в системе принятия инвестиционных решений на рынке ценных бумаг - Новиков, М.В. (Штучний інтелект, 2010)
В основе процесса принятия решений на фондовом рынке в условиях неопределенности второго рода возможен комплексный подход, состоящий из взаимосвязанных по критерию оптимума полезности моделей Фридмана – Сэвиджа и модели оптимума номинала. В этой системе моделей используется гребенчатый фильтр в качестве согласующего устройства. Гребенчатый фильтр строится на основе предпосылок и допущений о составе и структуре сигнала, к которому можно отнести информацию, формируемую в рамках процесса функционирования фондовой биржи. В основу процесу прийняття рішень на фондовому ринку в умовах невизначеності другого роду покладено комплексний підхід, що складається з взаємозв’язаних за критерієм оптимуму корисності моделей Фрідмана – Севіджа і моделі оптимуму номіналу. У цій системі моделей використовується гребінчастий фільтр як узгоджувальний пристрій. Гребінчастий фільтр будується на основі передумов і допущень про склад і структуру сигналу, до якого можна віднести інформацію, що формується в рамках процесу функціонування фондової біржі. Decision making on stock market in condition uncertainty of the second form will be based on complex method. This method is conclusion in using model of utility of Freedmen – Sawidge and model of optimum of nominal which is relative. In this case decision making is realize with use information filter constructing on based these models. Pectinated filter is using as coordination conformation of filtration processing from over of information stream. Pectinated filter is constructed on base of theoretical premises and assumptions about consistency and structure of signal, which is distinguish from noise of uncertain nature. Signal far filter is discrete on time and is characterize of own periodical formation. The information about functionary of stock exchange is characterized as that signal. Stock exchange is institute of stock market and so it fulfill the function of regulate of conditions stock market based on information stream. Herewith the actual task is allotment information for affective decision making. The solving these task is perhaps with using information filter is giving optimizes process selection from existing alternative position of stock market, based on model of utility of Freedmen – Sawidge, model of optimum of nominal and pectinated filter.